GLOBALIZATION AND THE SPREAD OF THE ENGLISH LANGUAGE - XIDIROVA MOHINUR SHUHRAT QIZI (TADQIQOTLAR, 2025)
Abstract This article provides an in-depth examination of how globalization has facilitated the global spread of the English language. It investigates the historical evolution of English dominance from the colonial era to the digital age, emphasizing the economic, cultural, political, and technological forces that have shaped its international status. The article also evaluates the consequences of English expansion for linguistic diversity, cultural identity, and global communication. Furthermore, it explores the rise of ’World Englishes,’ the transformation of English into a global resource rather than the property of native speakers, and the challenges this creates for education systems around the world. The study concludes by stressing the importance of multilingualism in preserving cultural heritage while benefiting from the advantages English provides in a globalized society.